Structural transformation, inequality dynamics, and inclusive growth in Bangladesh - Selim Raihan; Sunera Saba Khan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The Bangladesh economy has undergone significant structural changes over the last four decades. The share of agriculture in GDP has declined, while the significance of industry and service sectors has increased. These structural changes have been associated with persistent challenges such as lack of diversification, poor working conditions, low productivity, and high degree of informality, obstructing the progress towards inclusive economic growth. Though manufacturing is now an overwhelmingly salient component of Bangladesh's export composition, this is due primarily to the rapid expansion of the ready-made garments sector: the performance of other industries has been rather weak. In order to become a sustained, inclusive driver of economic growth and employment creation, the manufacturing sector needs to focus on expanding and diversifying its base. This study looks at the major challenges, both policy-induced and structural, for the required structural transformation in the Bangladesh economy, aiming to tackle inequality and promote inclusive growth.
Keywords: O14; O25; O40; O53; 330; Bangladesh; structural transformation; inclusive growth; inequality; ready-made garments